MAIN WAYS TO STRENGTHEN THE INTEGRATION OF THE BANKING AND REAL SECTORS - Suleymanov Ilnur Radikovich (Journal Park Publishing, 2022)
The article reveals ways to strengthen the integration and the banking system with the real sector of the economy. In modern geo-financial situations in the global capital market, the processes of strengthening integration and play an important role in stable mutually beneficial evolutionary development and ensuring financial stability and security of two important sectors. As part of the study in this area, universal scientific and practical proposals are presented to strengthen the integration of the banking system with the sectors of the real sector of the economy.
Keywords: banking, real sector, integration